Public health leadership: a framework inspired by timeless lessons from 500 years of the Jesuit tradition - Chyu, Laura; Grinshteyn, Erin G.; Vian, Taryn; S.J., Timothy Godfrey (Frontiers in Public Health, 2025)
The complex and dynamic nature of public health challenges calls for public health leaders who are able to respond with agility, insight, and integrity. In addition to technical expertise and skills, effective public health leadership requires ethical decision-making, collaborative partnerships, and a commitment to justice. Traditional leadership models often fall short in capturing the population-based aspects of public health and integrating a spiritual approach. This conceptual paper examines Jesuit principles and practices and how they can be applied to public health practice and leadership. The proposed framework outlines ten leadership principles: inclusive leadership, service to others, care for the whole person (cura personalis), striving for the greater good (magis), self-awareness, discernment in decision-making, cross-sectoral and community partnerships, global citizenship, lifelong learning and growth, and adaptability and innovation. This Jesuit-inspired framework offers a spiritual and values-based approach to cultivating compassionate, resilient, and effective public health leaders. It can be applied in academic and workplace settings to strengthen leadership training and guide strategic decision-making. By adopting and adapting Jesuit principles, public health leadership can be conceptualized as an inclusive, mission-driven practice committed to health equity and social justice.